Wnt Signaling Protects against Paclitaxel-Induced Spiral Ganglion Neuron Damage in the Mouse Cochlea In Vitro - Wang, Xue (Biomed Res Int, 2019)
It has been reported that paclitaxel administration could cause sensorineural hearing loss, and Wnt activation is important for the development and cell protection of mouse cochlea. However, the effect of Wnt signaling in spiral ganglion neurons (SGNs) damage induced by paclitaxel has not yet been elucidated. In this study, we explored the effect of paclitaxel on SGNs in the mouse cochlea and the neuroprotective effects of Wnt signaling pathway against paclitaxel-induced SGN damage by using Wnt agonist/antagonists in vitro. We first found that paclitaxel treatment resulted in a degenerative change and reduction of cell numbers in SGNs and induced caspase-mediated apoptosis in SGNs. The expression levels of β-catenin and C-myc were increased, thus indicating Wnt signaling was activated in SGNs after paclitaxel treatment. The activation of Wnt signaling pathway protected against SGN loss after exposure to paclitaxel, whereas the suppression of Wnt signaling in SGNs made them more vulnerable to paclitaxel treatment. We also showed that activation of Wnt signaling in SGNs inhibited caspase-mediated apoptosis. Our findings demonstrated that Wnt signaling had an important role in protecting SGNs against paclitaxel-induced damage and thus might be an effective therapeutic target for the prevention of paclitaxel-induced SGN death.